Análise de instrumentos de avaliação da competência informacional voltados para a educação superior - Santos, Camila Araújo dos [UNESP] (2011)
The information literacy assessment is a burning issue although little explored in Brazil. In the context international, there are some instruments to verify information skills of different groups of people, they are a diagnose to plan and apply activities of information skill formation by librarians and teachers. Among them we highlight Beile Test of Information Literacy for Education – B-TILED of the University of Central Florida, the instrument of the Working Group on Library Instruction of the Subcommittee on Libraries of the Conference of Rectors and Principals of Quebec Universities – CREPUQ, from Canada, the Information Competency Proficiency Exam from the project Bay Area Community Colleges Information Competency Assessment Project, and the instrument from the St. Olaf College, The First Year Information Literacy in the Liberal Arts Assessment (FYILLAA) Project. In this manner, we aim at analyzing these instruments in a general scope. In a more specific context, we aim at identifying the information skills mentioned by each of them; the types of questions they use; the way of analyzing data; reports generated by the system; to comparate the results with literature, do bibliographic survey of articles dealing the methods and tools that have been used in information literacy assessment; and develop guidelines for developing assessment tools of information literacy for higher education. The analysis of data was carried out by using the Content Analysis technique. The results show the instruments were focused on the skills related to the identification of the terms of information need, to the formulation and construction of strategies to search available in the parameter two of the Association of College and Research Libraries (ACRL); differentiation of sources (parameter one); evaluation and selection of information sources and selection of information on the theme to be researched... Complete abstract click electronic access below)